Attitude of oil palm smallholders towards Ganoderma disease - Assis Kamu; Bonaventure Boniface; Abdul Rahim Awang; Affendy Hassan; Mohammad Amizi Ayob; Siti Kalsom Yulo (2016)
This study was conducted to identify the attitude of oil palm smallholders towards Ganoderma disease. The data for this cross-sectional survey were collected through face-to-face interview by using structured questionnaire. A total of 1010 oil palm smallholders have been interviewed during the data collection. The data collected was analyzed by using descriptive analysis, factor analysis, and comparison test using non-parametric tests. The results of factor analysis show that there were three main components of attitude, namely lack of exposure towards the disease (Component 1), difficult to detect the disease (Component 2), and negative effect of the disease on the net profit (Component 3). Comparison test using non-parametric tests show there were significant differences in the summed score of all the components across the categories of the selected socioeconomic characteristics The findings of this study may useful to the relevant authorities in identifying strategic programs to improve the knowledge as well as the skills of oil palm smallholders in managing Ganoderma disease.